2020
DOI: 10.1007/s10853-020-05109-0
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of steels: a review of achievements and challenges

Abstract: Metal additive manufacturing (AM), also known as 3D printing, is a disruptive manufacturing technology in which complex engineering parts are produced in a layer-by-layer manner, using a high-energy heating source and powder, wire or sheet as feeding material. The current paper aims to review the achievements in AM of steels in its ability to obtain superior properties that cannot be achieved through conventional manufacturing routes, thanks to the unique microstructural evolution in AM. The challenges that AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(153 citation statements)
references
References 211 publications
1
99
0
2
Order By: Relevance
“…Additive manufacturing (AM) has been considered to be a promising technology for producing a variety of complex components in a relatively short time [ 1 , 2 , 3 , 4 , 5 , 6 ]. Traditional AM processing of metals mainly focuses on powder bed fusion (PBF) methods such as selective laser melting (SLM) and electron beam melting (EBM) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) has been considered to be a promising technology for producing a variety of complex components in a relatively short time [ 1 , 2 , 3 , 4 , 5 , 6 ]. Traditional AM processing of metals mainly focuses on powder bed fusion (PBF) methods such as selective laser melting (SLM) and electron beam melting (EBM) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the Fe2O3 and Cr2O3 layers was a primary factor for an improvement in the corrosion resistance, so the extended oxidation time Stašić and Božić examined the corrosion behavior of SLM 316L with an additional 1 wt.% NiB by measuring the weight loss in a 5% HCl solution [31]. The weight losses of sintering the 316L and the 316L-NiB samples were 1.2 and 1.3 g/m 2 •h, which indicated that the addition of NiB negligibly lowered the corrosion resistance of the base 316L material. SLM 316L as-manufactured samples, which were non-oxidized, and thermal oxidized samples, which were under an atmospheric condition of 700 • C for 150, 200, and 250 h, were prepared by Harun et al [32].…”
Section: Corrosion Behaviors Of Slm 316 Ss In Miscellaneous Solutionsmentioning
confidence: 99%
“…The advantages of AM over traditional manufacturing methods are that very complex parts can be fabricated directly from a CAD model with minimal waste generation, using less time. These advantages are sufficient for many researchers to study AM to increase the efficiency of sophisticated operations, and its market value is expected to reach $21 billion by the end of 2020 [2]. Therefore, many studies are ongoing, which compare the mechanical properties, corrosion behavior, and microstructure of the metals that are produced by AM or traditional manufacturing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing costs, associated with post-production, it has to be considered that the end product is of the "near-net-shape" type, starting from a virtual model 63 . Additive manufacturing has been applied to maraging steels with exciting and promising results [64][65][66] . Figure 13 shows a typical microstructure of a maraging 300 steel processed by additive manufacturing using selective laser melting (SLM), wherein the fine microstructure can be observed, apart from the low level of defects, such as few pores 67 .…”
Section: Future Perspectivesmentioning
confidence: 99%